USING SONG AS MEDIA IN TEACHING ENGLISH - Syamsiah Depalina Siregar (Universitas Muhammadiyah Tapanuli Selatan, 2018)
This study was aimed at first investigating whether or not the use of songs significantly give effect as media in teaching English. Second, the difficulties faced by the students in learning English were also investigated. This quasi experimental research involved two classes of students of agriculture in UMTS. The data were collected through pretest, posttest and questionnaires. In analyzing the collected data, quantitative research method was employed. Furthermore, the data taken from questionnaires were also investigated to find out the difficulties faced by the students in using songs as media in learning English. The study found that the use of songs likely improves students’ motivation in learning English. It was evidenced by tobt (6.542) that greater than tcrit. As the result of the study, the null hypothesis of this research was rejected; the use of songs is likely to give effecct in learning English.